Versatility of sulfonated poly (vinylidene fluoride‐co‐hexafluoropropylene) membranes incorporated with sulfonated octaphenyl polyhedral oligomeric silsesquioxane for vanadium redox flow battery applications. Issue 28 (20th May 2022) - Divya, Kumar; Rana, Dipak; Sri Abirami Saraswathi, Meenakshi Sundaram; Nagendran, Alagumalai
Abstract: Hybrid membranes are fabricated using the blends of sulfonated poly (vinylidene fluoride‐co‐hexafluoropropylene) (SPVDF‐co‐HFP) and sulfonated octaphenyl polyhedral oligomeric silsesquioxane (SOPS) as an alternate for expensive Nafion in vanadium redox flow battery (VRFB) applications. The FT‐IR and TEM investigation indicates the successful sulfonation of OPS and uniform distribution of SOPS. The morphological study of hybrid membranes by SEM–EDX and FESEM revealed the excellent dispersing ability of SOPS on a SPVDF‐co‐HFP matrix. The physicochemical analysis of SPVDF‐co‐HFP/SOPS membranes demonstrated an increase in hydrophilic ion‐exchangeable sites. The SPVDF‐co‐HFP/SOPS (0.5 wt.%) membrane displayed a maximum proton conductivity of 6.27 × 10 −3 Scm −1 at 80°C because of strong hydrogen bond formation between SPVDF‐co‐HFP and SOPS facilitates proton migration. Besides, the cage‐like structure of SOPS effectively shields vanadium‐ion permeation to 1.21 × 10 −8 cm 2  min −1 and thus, showed a maximum membrane selectivity of 43.05 × 10 4 Scm −3  min. Overall, the hybrid membranes of SPVDF‐co‐HFP/SOPS were considered to be a better substitute for Nafion in VRFBs. Abstract :